Hubungan Pengetahuan dengan Sikap Ibu Preeklampsia tentang Kebutuhan Antenatal Care di Kecamatan Badas Kabupaten Kediri - Oktalia Citra Rahayu; Ratna Hidayati; Didit Damayanti (JURNAL ILKES : Jurnal Ilmu Kesehatan, 2018)
The highest cause of maternal mortality is eclampsia with 31% rating, researchers found almost 75% of mothers did not know the signs of preeclampsia even some mothers only check their pregnancy if there is a grievance only. Aims of this study was to analyze the relationship of knowledge and attitude of pre eclampsia mother about antenatal care needs in Badas sub-district, Kediri regency. This research use correlation design and cross sectional approach, a total of 26 respondent were found with total sampling technique. Which knowledge of mother with pre eclampsia as independent variable, and the attitude as its dependent. The data were analyzed with Spearman Rank, the result showed that most (65,4%) knowledge of preeklampsia mother about antenatal care needs was good, half (50%) attitude of preeclampsia mother about antenatal care requirement was positive and negative. Researcher found Pvalue = 0,003, <α = 0,05 and r = 0,567. Thus, there is a correlation between knowledge with attitude of mother of preeclampsia about antenatal care requirement with medium correlation level. The existence of relationship between knowledge and attitude on pre eclampsia mother with a good knowledge level in antenatal care needs can influence mother comprehension in deciding and choosing the attitude that will be taken. Researcher expected every mother can share their experience and information to another mother and society especially to pregnant womans, researcher hope by sharing description and information about pre eclampsia with everyone will be helpful and we can overcome several of pregnancy problem based on the experience from several people.